The Impact of Recourse Right in Electronic Commerce Contracts on the Principle of Freedom Contracts - Bouakaz, Khalil; Hajj Ali, Badr Eddin (Journal of Legal Studies and Researches, 2022)
One of the most important guarantees is the right of termination close of the contract. In this case many legislations give the right to the consumer of the electronic commerce contract by giving him the permission –in limited period- of canceling or terminating the contract